2022
DOI: 10.1093/cid/ciac160
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Severe Acute Respiratory Syndrome Coronavirus 2 Antigens in Plasma of Pediatric Patients With Acute Coronavirus Disease 2019 or Multisystem Inflammatory Syndrome in Children Using an Ultrasensitive and Quantitative Immunoassay

Abstract: Background Detection of SARS-CoV-2 antigens in blood has high sensitivity in adults with acute COVID-19, but sensitivity in pediatric patients is unclear. Recent data suggest that persistent SARS-CoV-2 spike antigenemia may contribute to multisystem inflammatory syndrome in children (MIS-C). We quantified SARS-CoV-2 nucleocapsid (N) and spike (S) antigens in blood of pediatric patients with either acute COVID-19 or MIS-C using ultrasensitive immunoassays (Meso Scale Discovery). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…[3][4][5] Spike protein antigenemia has also been inconsistently observed in children with SARS-CoV-2 associated multisystem inflammatory syndrome (MIS-C). 6,7 Due to limited evidence, the clinical utility of detecting and quantifying SARS-CoV-2 proteins in peripheral blood from children with SARS-CoV-2 is uncertain. We, therefore, sought to determine whether antigenemia is a marker of acute SARS-CoV-2 infection or is associated with disease severity or clinical manifestations in children.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Spike protein antigenemia has also been inconsistently observed in children with SARS-CoV-2 associated multisystem inflammatory syndrome (MIS-C). 6,7 Due to limited evidence, the clinical utility of detecting and quantifying SARS-CoV-2 proteins in peripheral blood from children with SARS-CoV-2 is uncertain. We, therefore, sought to determine whether antigenemia is a marker of acute SARS-CoV-2 infection or is associated with disease severity or clinical manifestations in children.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is plausible that the presence of both viral antigens and antibodies may be required for a direct antibody-mediated cardiac pathology, which is supported by findings of 2 studies from Yonker et al showing viral antigenemia in patients with MIS-C and vaccine myocarditis . However, this is contrary to the findings of another study showing that most patients with MIS-C have undetectable levels of SARS-CoV-2 nucleocapsid and spike antigens in their blood …”
Section: Discussionmentioning
confidence: 98%
“…23 However, this is contrary to the findings of another study showing that most patients with MIS-C have undetectable levels of SARS-CoV-2 nucleocapsid and spike antigens in their blood. 24 As the clinical profile, cardiac involvement, and disease severity of MIS-C and vaccine myocarditis are very different, these 2 conditions could potentially be caused by different dysregulated immune responses. MIS-C is associated with a systemic hyperinflammatory response and excessive cytokine release, which, along with rapid severe cardiac dysfunction that reverses quickly with immunomodulation, suggests that increased pro-inflammatory cytokines (eg, interlukin 6, interferon γ, tumor necrosis factor α) could be contributing to the cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, N and S antigens in acute COVID-19 did not correlate strongly with RT-PCR [ 29 ]. On the other hand, the use of a novel method (MSD S-PLEX CoV-2 N and S assays) demonstrated that, during the early hospital course, SARS-CoV-2 N and S antigens are detectable in blood in most pediatric patients with acute COVID-19, but in few cases of MIS-C [ 30 ]. Therefore, the RT-PCR method for COVID-19 detection is not exclusive to MIS-C diagnosis, and serology and epidemiological linkage are also considered.…”
Section: Mis-c Case Definition and Clinical Manifestationsmentioning
confidence: 99%